The Contribution of Islamic Religious Education Empowered Teachers in Enhancing Students' Academic and Character Development Through Islamic Education - Rahmatilla, Tari; Nasrullah, Yufi Mohammad; Usman, Asep Tutun; Nazib, Fiqra Muhamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the contribution of the Islamic Religious Education Empowered Teachers in improving students' learning abilities at SMP Negeri 1 Garut, Indonesia. Using a phenomenological qualitative approach, data were collected through in-depth interviews with one Islamic Religious Education teacher and five students. The findings of the study show that the teacher plays an important role in creating a religious and supportive school environment through various spiritual programs, such as Dhuha prayers, routine Qur'an recitation, and congregational Zuhur prayers. Additionally, the teacher introduced an innovative environmental initiative, the